Penerapan Algoritma Apriori Dalam Penjualan Produk - Br Sembiring, Yulia Ananda; Sembiring, Emy Alfiani (Jurnal Sains dan Teknologi Informasi, 2023)
Micro, small and medium enterprises (UMKM) in the shopping sector have great potential to meet the needs of people in the middle to lower and upper economic categories. How ever, small shopsoften experience problems in managing the supply of goods or materials needed by customers. This can lead to a lack of goods that customers want, and ultimately disappoint them. There fore, inventory control is very important in maintaining customer satisfaction and business continuity small shops. To help overcome this problem, research can be carried out using the Apriori algorithm. This algorithm can help identify the most sold products, so small shops can manage optimal inventory. Thus, small shops can meet customer needs effectively and efficiently, and avoid product shortages that can interfere with customer satisfaction. In research, several variables are used to collect data, such as transaction date,product name, and the amount of sales/purchases. This data can then be analyzed using the Apriori algorithm, so that it can be concluded that final result of the confidence or 2 itemset is that if you buy sugar, you will buy rice and if you buy eggs, will you buy rice